UBC gene family and their potential functions on the cellular homeostasis under the elevated pCO2 stress in the diatom Phaeodactylum tricornutum. (April 2023) - Ma, Wanying; Du, Hua; Kazmi, Syed Shabi Ul Hassan; Chen, Jichen; Chen, Weizhou; Fan, Yanmei; Liu, Zidong; Luo, Haodong; Fang, Hao; Wang, Zhen; Liu, Xiaojuan
Graphical abstract: Highlights: 18 PtUBCs were identified into 5 independent clades. Cis -acting elements related to stress responses were characterized from PtUBC s. PtUBC15, PtUBC16 and PtUBC7 might have a negative effect during the ERAD pathway. The misfolded/ unfolded proteins might be degraded by the ERAD mechanism. Abstract: Ocean acidification (OA) as a result of more and more anthropogenic CO2 release, has already been referred to a severe ecological environmental issue. OA would destroy the balance of ocean carbonate buffering system and have negative effects on marine primary producers. Diatom Phaeodactylum tricornutum is one of the most important primary producers in the ocean, and it is susceptible to the elevated p CO2 stress. Under the elevated p CO2 stress, endoplasmic reticulum-associated degradation (ERAD) and its important components Ubiquitin-conjugating enzymes (UBCs) are pivotal to sustain cellular homeostasis. However, systematic investigation regarding phylogenetic relationships of UBC gene family, expression profiles under the elevated p CO2 stress and their potential functions on the cellular homeostasis of P. tricornutum remain poorly understood. In this study, a genome-wide analysis of PtUBC gene family was performed. It was shown that 18 PtUBC genes were unevenly distributed to the 14 chromosomes of total 33 chromosomes in P. tricornutum . Phylogenetic analysis showed that 18 PtUBC proteins were divided into 5 groups and each of them contained different conserved motifs. Besides, lots of cis -acting elements related to diverse stress responses were identified from PtUBC genes. Remarkably, transcriptomic analysis revealed that 3 PtUBC genes ( PtUBC15, PtUBC16 and PtUBC7 ) were downregulated under the exposure to elevated p CO2 level, while the other 15 PtUBC genes did not have significant expression. Meanwhile, the model of endoplasmic reticulum-associated degradation (ERAD) mechanism was displayed, explaining that the misfolded/ unfolded proteins under the elevated p CO2 stress would be accumulated and then degraded via the ERAD mechanism to sustain the cellular homeostasis. The downregulated PtUBC genes might have a negative effect on the ERAD mechanism. Overall, this study provided an important foundation for further understanding of possible functions of PtUBC genes, especially on the cellular homeostasis, and the regulatory mechanism of PtUBCs on the diatom response to different environmental stresses.